Rancang Bangun Sistem Informasi Manajemen Perpustakaan Berbasis Cloud Server - Restu Abdi Ariadi; Sry Wulandari (Lembaga Publikasi Ilmiah Nusantara, 2025)
The development of information technology encourages educational institutions to adopt integrated systems that can improve the effectiveness of resource management, including library services. This study aims to design and build a cloud server-based Library Management Information System that can provide real-time data access, improve operational efficiency, and support user mobility. The system development method uses the Waterfall model, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The system is designed with key features such as book collection management, catalog search, digital borrowing and returning, and monitoring usage statistics. A cloud server architecture is used to ensure library data is stored centrally, securely, and can be accessed from various devices without location restrictions. Implementation results show that the system can speed up the service process by up to 40% and minimize recording errors compared to manual methods. Black box testing shows that all functions run as needed. In addition, the system makes it easier for librarians to perform data collection and improves the user experience through faster and more responsive service access. This research is expected to become a modern solution for educational institutions in optimizing cloud technology-based library services.